'I Consider Myself a Political Prisoner': The Long and Strange Journeys of American Rebels Enmeshed in Ironies of the Athletes' Rights Crusade. Issue 8 (15th July 2022) - Sikes, Michelle M.; Fredericks, Jacob J.; Rodríguez, Paulina A.; Macedo, Emmanuel; Poorman, Michael; Lyons, Matthew; Pandit, Rucha; Dyreson, Mark
ABSTRACT: Flaunting international anti-apartheid bans, two groups of American track and field 'rebels' toured South Africa in the late 1980s. In defending their incendiary treks, they asserted their rights both to act on their own political principles and to earn a paycheck. Heavily criticized by a global coalition that supported the South African athletic embargoes, they were punished with long suspensions and public humiliation. A few of the 'rebels' remained in South Africa after the tours, most prominently world-class javelin thrower Tom Petranoff who moved his family to the apartheid state and continued his career in the only nation in the world that would still allow him to compete. As apartheid unexpectedly and rapidly crumbled in the early 1990s, Petranoff became a South African citizen, sought a place on the South African 1992 Olympic team that returned to the games for the first time since 1960, and touted his particular, libertarian doctrine of athletes' rights. Petranoff painted himself as a 'political prisoner' shunned by both his native US homeland and the new multi-racial government emerging in South Africa in the post-apartheid era. His career offers a window into the complexities of national and international sport in confronting apartheid regimes.